Urgensi Pembentukan Aturan Cyber Notary Berkaitan Dengan Penggunaan Sidik Jari Elektronik - Wahyudi, Dian Barry; Swardhana, Gde Made (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 8 No 01 (2023)DO - 10.24843/AC.2023.v08.i01.p12, 2023)
The absence of regulations regarding the attachment of fingerprints electronically will create a norm vacuum. The Amendment UUJN has required the appearers to attach their fingerprints so that there is not only a signature in the minutes of the deed. Therefore, the aim of this study is to examine the solicitation of the cyber notary in relation to the use of electronic fingerprints in making deeds, so the effectiveness of the implementation of cyber notary within the scope of the notary's duties. This research uses normative research that focuses on positive legal rules, and uses statutory as well as conceptual approaches. The application of cyber notary relating to the use of electronic fingerprints in making the deed cannot be carried out because there are no arrangements related to electronic fingerprints. The implementation of Cyber ??Notary within the Scope of the Notary Position has not been running properly or is not effective because the implementing regulations related to cyber notary have not been issued.